EP 2. Pyramidal tract FA predicts motor outcome in subacute stroke patients after a three week period of arm ability training for ADL-relevant hand motor tests. Issue 9 (September 2016) - Domin, M.; Roschka, S.; Horn, U.; Platz, T.; Lotze, M.
Abstract : Objective: Outcome prediction after motor stroke for the acute to subacute phase can be consulted for individual therapy modification. For the outcome of severely impaired patients the intactness of the pyramidal tract descending from the lesioned hemisphere (ipsilesional; i ) has been described as an important parameter for upper limb strength as a measure of motor outcome (Stinear et al., 2012 ). In addition, in chronic stroke fractional anisotrophy (FA) of the pyramidal tract is predictive for hand motor impairment in strength (Lindenberg et al., 2010 ). In this study we tested whether this does also holds true for the subacute phase and for activity of daily living (ADL) relevant testing of arm activities, i.e. finger and hand dexterity. Methods: Thirteen patients after first time stroke (4.7 ± 1.9 weeks after stroke; 9 with left hemispheric lesion; age 60 ± 12.6 years, NIHSS: 2.69±1.8; Edinburg handedness 81.35 ± 34.7) were recruited at the BDH-hospital of Greifswald. They had small lesions (predominantly subcortical; volume: 7.17±15.8 ccl) and mini mental status revealed no severe cognitive impairments (average score 27). Patients underwent a three week course of arm ability training (1 hour per day, 5 days a week) (Platz et al., 2009 ) in addition to the standard inpatient rehabilitation therapy. MRI and motor performance (Box and Block test; Nine Hole Peg test) were measured before and after training. MRI comprised of high resolution T1-weighted imaging (MPrage-sequence) and a diffusion weighted imaging (64 directions; MDDW-sequence) using a 32 channel head coil with a 3 Tesla MRI scanner (Siemens, Erlangen). The average FA was evaluated for the pyramidal tract between the affected hand area of the primary motor cortex (M1 i ) to the internal capsule and M1i crossing to the contralesional ( c ) pons. FSL was used for calculating average FA over tract. Results: Motor tests for the affected hand significantly improved during training (NHP: t  = 3.87; p  < 0.002; BB: t  = 4.58; p  < 0.001). FA of the pyramidal tract was lower for the affected than for the unaffected hemisphere (M1 i to internal capsule: t  = 4.83; p  < 0.001; M1 i to pons c : t  = 4.83; p  < 0.001). FA of the pyramidal tract descending from the affected M1 was associated with later motor outcome for NHP (M1 i to internal capsule: r  = −0.57; p  = 0.04; M1 i to pons c : r  = −0.87 p  = 0.02) and BB (M1 i to internal capsule: r  = 0.68; p  = 0.01; M1 i to pons c : r  = 0.84 p  = 0.04). Conclusion: Intactness of pyramidal tract is capable for predicting activity of daily living relevant hand motor outcome after comprehensive and specific arm motor training in subacute stroke patients.